P131 Targeting activated synovial fibroblasts using photodynamic therapy in human rheumatoid arthritis synovial tissue. (March 2019) - Dorst, DN; Rijpkema, M; Buitinga, M; Laverman, P; Brom, M; Bos, DL; Freimoser-Grundschober, A; Klein, C; Walgreen, B; Van der Kraan, PM; Gotthardt, M; Koenders, MI
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Activated synovial fibroblasts (ASF) play an important role in the pathogenesis of rheumatoid arthritis (RA). They contribute to the pro-inflammatory environment in the joint and degradation of cartilage and bone. Depleting ASF could ameliorate both these hallmarks of RA. ASF are characterized by the expression of fibroblast activation protein (FAP). Objectives: Here, we investigated the potential of FAP-targeted photodynamic therapy (tPDT) using the photosensitizer IRDye700DX conjugated to the anti-FAP antibody 28 H1 (28H1–700DX) to selectively kill these cells. Methods: To demonstrate the proof-of-concept of FAP-based tPDT in ex vivo human tissue, RA synovial tissue obtained during joint replacement surgery was trypsin digested and fibroblasts were cultured for at least 5 passages. Cells were incubated with or without 1 ug/well 28H1–700DX for 4 hour, washed with PBS and either exposed to 690 nm light or not exposed. A luminescent cell viability assay (CellTiter-Glo) was used to measure cell viability. In parallel, 6 mm biopsies of synovial tissue were taken and used for FAP-based tPDT (n=8 patients). They were subjected to tPDT as described above and formalin fixed after 1 hour. To measure cell death, 5 µm paraffin slices were stained for FAP, gamma-H2AX and caspase-3 expression for activated fibroblasts, DNA double-strand breaks and early apoptosis, respectively. Results: FAP-tPDT performed on the cultured fibroblasts showed a light dose dependent increase in cell death when incubated with 28H1–700DX for 4 hour. Cell viability was not affected when cells were incubated with 28H1-700DX without illumination (101.37%±3.9% remaining compared to 100%±5.07% in the normalized control). Radiant exposure of 17.6 J/cm 2 did not significantly decrease cell viability (6.4%±9.8% decrease, ns). Radiant exposures of 52.8, 105.6 and 158.4 J/cm 2 significantly decreased cell viability (38.6%±6.9%, 67.5%±10.9% and 80.6%±5.8% respectively, p<0.001 for all). After FAP-tPDT, the human synovial biopsies showed a significantly increased staining of the caspase-3 marker, but not of gamma-H2AX (Friedman's ANOVA, p=0.007 and p=0.810 respectively). Pairwise comparison showed that caspase-3 scores were significantly higher in biopsies treated with tPDT compared to those incubated with buffer (p=0.009). Conclusions: FAP-tPDT induces cell death of FAP-positive activated fibroblasts in synovial tissue from RA patients. This is a first indication that FAP-targeted PDT can be a feasible new treatment strategy in RA. Disclosure of Interest: D. Dorst: None declared, M. Rijpkema: None declared, M. Buitinga: None declared, P. Laverman: None declared, M. Brom: None declared, D. Bos: None declared, A. Freimoser-Grundschober Grant/research support from: support in kind, C. Klein Grant/research support from: support in kind, B. Walgreen: None declared, P. Van der Kraan: None declared, M. Gotthardt: None declared, M. Koenders: None declared.